PENGARUH OPINI AUDIT, KINERJA KEUANGAN DAN TINGKAT PENGUNGKAPAN LAPORAN KEBERLANJUTAN TERHADAP AUDIT REPORT LAG - Febriansyah, Farhan; Oktaviani, Ayu Aulia (Jurnal Akuntansi Trisakti, 2026)
This study aims to analyze the effect of audit opinion, financial performance, and Sustainability Reports on audit report lag in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. The research method used is a quantitative approach with secondary data in the form of audited financial statements and Sustainability Reports. The sample was determined using purposive sampling and obtained 65 companies over three years, resulting in a total of 195 observations. The analysis was performed using multiple linear regression. The results showed that audit opinions had no effect on audit report lag. Profitability had negative effect on audit report lag, indicating that more profitable companies published their financial reports faster. Meanwhile, solvency had no effect on audit report lag. On the other hand, Sustainability Reporting level do not have effect. This study contributes to regulators, auditors, and investors regarding the importance of transparency, financial health, and sustainability disclosure in improving financial reporting efficiency.